X+99=93

Simple and best practice solution for X+99=93 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+99=93 equation:


Simplifying
X + 99 = 93

Reorder the terms:
99 + X = 93

Solving
99 + X = 93

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-99' to each side of the equation.
99 + -99 + X = 93 + -99

Combine like terms: 99 + -99 = 0
0 + X = 93 + -99
X = 93 + -99

Combine like terms: 93 + -99 = -6
X = -6

Simplifying
X = -6

See similar equations:

| 4(3r-4)=3(r+9)+2 | | b-1/2=2 | | 3(Y+9)+3Y=30 | | 10+6a=-104 | | f(x)=3x^2+5x+7 | | X/2-430 | | 2(t+8)=8 | | 9x-6=7y+3x | | 5y+6q=20 | | 200+.62x=379.8 | | 4x^2-10x-126=0 | | 2x-x=-1+3 | | 200-.62x=379.8 | | 24a^3b^2-16a^2b^3/8ab | | 5y-8/8-5y | | 5(4a+3b)5(2a+3b)= | | 2/5x-1-9/4x-6 | | 25x-21=16x-4x | | 3(y+9)1y=30 | | (2x-5)/(x-1)3 | | sin(2x)-(.259)=cos(x)-(.978) | | Y=-x/4-3 | | 9(t+5)=5 | | 6x^2+4x+7=7 | | (2x-5/x-1)3 | | -3d=36 | | 7+ax-9=-6 | | X-2/5=3.5 | | (2h-3i)(h+4i)= | | 71.4=6(m+3.6) | | 2(3(1.6)+2)=2x-1+x | | 2(x-4)+1x=10 |

Equations solver categories